2007
DOI: 10.1002/jmv.21025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus types 6, 11, 16, 18, 31, and 33 in a cohort of Greek women

Abstract: To study HPV prevalence and HPV types 6, 11, 16, 18, 31, and 33 distribution in cervical smears in a cohort of Greek women. One thousand six hundred thirty-six samples were cytologically evaluated and molecularly analyzed, by PCR based assay. Abnormal cytology was identified in 997 women and 75.4% of them were HPV DNA positive, while 639 had normal cytology and 24.6% were HPV DNA positive. HPV was detected in 62.9% of 256 ASCUS smears, 89.3% of 516 LSIL, 86.7% of 60 HSIL and 47.3% of 165 with cervical carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
2
12
2
6
Order By: Relevance
“…HPV16 together with HPV18 are known to be responsible for approximately 70% of the cervical cancer cases worldwide [6, 8, 9]. The prevalence of HPV18 has been reported in other studies, ranging between 1.8% and 16.3% [20, 21, 23, 27]. In agreement with the aforementioned studies, the prevalence of HPV18 in the present study was 4.1%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…HPV16 together with HPV18 are known to be responsible for approximately 70% of the cervical cancer cases worldwide [6, 8, 9]. The prevalence of HPV18 has been reported in other studies, ranging between 1.8% and 16.3% [20, 21, 23, 27]. In agreement with the aforementioned studies, the prevalence of HPV18 in the present study was 4.1%.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that at least 22.8% of women were infected with two or more HPV genotypes, in accordance with other studies reporting a prevalence of multiple infections in 11% to 50% of cases [21, 23, 34]. The clinical significance of co-infection with multiple HPV genotypes remains uncertain, with some reports showing that the clearance rate in immunocompetent women is not dependent on the number of genotypes involved in the infection [35].…”
Section: Discussionsupporting
confidence: 89%
“…This rate is slightly higher compared with previous results of our group in smaller samples (Agorastos et al, 2004(Agorastos et al, , 2005 and lower than these of other Greek studies in much smaller, selected populations (Agorastos et al, 1995;Kroupis et al, 2007;Panotopoulou et al, 2007).…”
Section: Discussioncontrasting
confidence: 82%
“…In Spain HPV 18 does not appear as common as in this current study [Cobo et al, 2009]. In contrast, HPV 18 was detected in a Greek study in a large proportion of women with cytological abnormalities [Panotopoulou et al, 2007]. Other studies showed that HPV 18 can be under-represented and other high-risk HPV genotypes over-represented in low-grade lesions as well as high-grade lesions in comparison to invasive cervical cancer [Smith et al, 2007].…”
Section: Discussioncontrasting
confidence: 72%